Lepidorhombus whiffiagonis ... - Bariche, Michel; Fricke, Ronald (Zenodo, 2020)
Lepidorhombus whiffiagonis (Walbaum 1792) —Megrim Taxonomy. First record from Lebanon as Symphurus whiffiagonis by Colloca & Lelli (2012: 38); subsequently recorded as Lepidorhombus whiffiagonis by Aguillar et al. (2018: 81). Distribution. Western Baltic Sea, North Sea, Mediterranean Sea, eastern Atlantic: Iceland and Norway south to Western Sahara. Conservation. IUCN: Global (NE); Med. (LC: 28 February 2008). Capture and threats: Unknown. Occurrence: Very rare. Low priority for conservation action. ... : Published as part of Bariche, Michel & Fricke, Ronald, 2020, The marine ichthyofauna of Lebanon: an annotated checklist, history, biogeography, and conservation status, pp. 1-157 in Zootaxa 4775 (1) on page 101, DOI: 10.11646/zootaxa.4775.1.1, http://zenodo.org/record/3983887 ...